PENGARUH PERMAINAN TRADISIONAL ASING - ASING TERHADAP HASIL BELAJAR PJOK SISWA KELAS III DI UPT SD NEGERI 35 LEANGE KECAMATAN LABAKKANG KABUPATEN PANGKEP - Rahman, Fatur; Ashar; Muh. Yusran Rahmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of traditional foreign games on the physical education (PJOK) learning outcomes of third-grade students at the UPT SD Negeri 35 Leange, Labakkang District, Pangkep Regency.This study was quantitative, employing a quasi-experimental approach with a pretest-posttest design. The subjects consisted of third-grade students divided into an experimental group and a control group. The experimental group received treatment in the form of physical education (PJOK) learning using traditional foreign games, while the control group used conventional learning methods. Data collection techniques included learning achievement tests, observations, and questionnaires. The learning achievement tests were used to determine students' abilities before and after the treatment, observations to monitor student learning activities, and questionnaires to assess students' responses to the implementation of traditional foreign games.The results showed that the average pretest score for physical education (PJOK) learning outcomes in the experimental group was 75, while the average posttest score increased to 86.5. Data analysis indicated an improvement in students' physical education learning outcomes after the implementation of traditional foreign games. Based on the results of the hypothesis testing, it was found that H₀ was rejected and Hₐ was accepted, so it can be concluded that there is a significant influence of the use of foreign traditional games on the physical education learning outcomes of grade III students at UPT SD Negeri 35 Leange, Labakkang District, Pangkep Regency.